INFLUÊNCIA DO pH DA ÁGUA NA GÊNESE DO CÂNCER POR INTOXICAÇÃO POR CÁDMIO: UM ESTUDO EXPERIMENTAL EM RATOS - Golghetto, Gisele Maria Soria (2013)
Introduction: Cadmium is a heavy metal, widely used in industry. It may give rise to the appearance of tumors in multiple organs. Objective: To evaluate the effect of the pH of the water in the genesis of cancer caused by cadmium. Material and methods: We used 98 Wistar rats were divided into seven groups: A - 15 rats that received solution of cadmium chloride (CdCl2 - 400mg / L) in drinking water with a neutral pH (pH 7.0), B - 15 rats that received CdCl2 (400 mg / L) in the drinking water at acidic pH (pH 5.0), C - 15 rats that received CdCl2 (400 mg / L) in drinking water with basic pH (pH 8.0), D - 15 rats that received water at acidic pH (pH 5.0), E - 15 rats that received water with basic pH (pH 8.0), F - 15 rats that received water at neutral pH (pH 7.0 ); G - 8 rats that received cyclophosphamide as a single dose (50mg/kg) on the first day of the experiment (positive control for micronucleus test). Rats of groups A-F were euthanized after 6 months and the group G, 24 hours after the start of the experiment. We removed liver, kidney, pancreas, prostate, seminal vesicles, testes, and bone marrow. Results: There were no pre-neoplastic or neoplastic in liver, kidney, pancreas, seminal vesicles and testes in all groups. Only animals exposed to cadmium showed prostatic intraepithelial neoplasia grade one, being more prevalent in group B (p<0.05), although there was no increase in micronuclei (p>0,05). Conclusion: The acidic pH contributed to the formation of precancerous lesions in the prostate gland of animals exposed to cadmium.